The Interplay between Circadian System, Cholesterol Synthesis, and Steroidogenesis Affects Various Aspects of Female Reproduction - Urlep, Ziga; Rozman, Damjana (Frontiers in Endocrinology, 2013)
Circadian aspect of reproduction has gained much attention in recent years. In mammals, it is very important that the timing of greatest sexual motivation is in line with the highest fertility. Peripheral clocks have been found to reside also in reproductive organs, such as the uterus and ovary. The timing signal from the SCN is suggested to be transmitted via hormonal and neural mechanisms, and could thus mediate circadian expression of target genes in these organs. In turn, estrogens from the ovary have been found to signal back to the hypothalamus, completing the feedback loop. In this review we will focus on the interplay between clock and estrogens. Estradiol has been directly linked with expression of Per1 and Per2 in the uterus. CLOCK, on the other hand, has been shown to alter estradiol signaling. We also present the idea that cholesterol could play a vital role in the regulation of reproduction. Cholesterol synthesis itself is circadially regulated and has been found to interfere with steroidogenesis in the ovary on the molecular level. This review presents a systems view on how the interplay between circadian clock, steroidogenesis, and cholesterol synthesis affect various aspects of mammalian reproduction.